The Influence of TikTok Social Media on The Emergence of Slang Language Used by Gen Alpha - Fatmasari, Agil Putri; Wardhani, Tiara; Roronias, Niken Ayu Agista; Oemara, Raka Pratama; Nasywan, Fadhlurrohman Ammar (KIRANA : Social Science Journal, 2025)
In today's digital era, TikTok has become a very popular platform among teenagers, allowing them to interact and express themselves through creative short videos. The use of slang on TikTok not only reflects the dynamics of communication between users but also shows how language can change and adapt rapidly along with technological developments. Through a qualitative approach, this study collected data from content containing Gen Alpha slang uploaded on TikTok, and analyzed the forms of slang that emerged. The results of the study show that slang used on TikTok tends to be acronyms, abbreviations, and borrowings from various languages, including English. This study also identifies factors that encourage the use of slang among Generation Alpha, such as the desire to socialize, build social identity, and follow trends. This study is expected to provide insight into the impact of social media on the development of language and communication among teenagers, as well as being a reference for social interaction in a digital context. The objectives of this study are: 1. To determine the influence of TikTok social media on the emergence of slang used by Gen Alpha 2. To find out examples of various slang used by Gen Alpha, 3. To find out the influence of slang used by Gen Alpha on the existence of Indonesia.